2019
DOI: 10.1186/s12879-019-3999-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and factors impacting outcome of Candida auris: a single center study from Pakistan

Abstract: Background An outbreak of Candida auris began globally in 2014 including Pakistan and since then it has emerged as a nosocomial multi-drug resistant pathogen. The aim of this study was to assess the clinical spectrum and outcome of patients, from a single center in Pakistan, in whom C. auris was isolated. Methods A retrospective study was conducted on 92 patients; ≥16 years with at least one culture positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 16 publications
6
34
1
5
Order By: Relevance
“…Candida auris can persist on different types of surfaces, including moist, dry, and plastic surfaces, with the potential of survival for up to 14 days [33][34][35][36][37]. The success of environmental decontamination was variable in the literature utilizing mostly materials and methods tested earlier against resistant Gram-positive and Gram-negative pathogens [17,21,38,39]. The use of high-concentration chlorine solutions in combination with hydrogen peroxide vapor or UV light for terminal decontamination has been suggested to be effective in controlling the transmission in some reports [17,19,21,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida auris can persist on different types of surfaces, including moist, dry, and plastic surfaces, with the potential of survival for up to 14 days [33][34][35][36][37]. The success of environmental decontamination was variable in the literature utilizing mostly materials and methods tested earlier against resistant Gram-positive and Gram-negative pathogens [17,21,38,39]. The use of high-concentration chlorine solutions in combination with hydrogen peroxide vapor or UV light for terminal decontamination has been suggested to be effective in controlling the transmission in some reports [17,19,21,40].…”
Section: Discussionmentioning
confidence: 99%
“…The success of environmental decontamination was variable in the literature utilizing mostly materials and methods tested earlier against resistant Gram-positive and Gram-negative pathogens [17,21,38,39]. The use of high-concentration chlorine solutions in combination with hydrogen peroxide vapor or UV light for terminal decontamination has been suggested to be effective in controlling the transmission in some reports [17,19,21,40]. The same protocol without UV light was used in our setting twice including when it was used for controlling a MERS-CoV outbreak, but this failed to have impact on the incidence of new C. auris cases.…”
Section: Discussionmentioning
confidence: 99%
“…C. auris infection occurs at a variety of clinical sites, including the bloodstream, wounds, and the urinary tract [6,12,13]. In addition, C. auris colonizes skin, nares, wounds, and urine, as a marker of disease risk [3,6,14].…”
Section: What Is the Clinical Presentation Of C Auris Infection?mentioning
confidence: 99%
“…There was a 318% increase in the number of reported C. auris infections in 2018 compared to rates from 2015-2017 [1]. Multiple studies examining C. auris infections from hospitals in India, Colombia, and New York found that 58-76% of these lead to invasive blood stream infections [2,8,9].…”
Section: New Emerging Fungal Threatsmentioning
confidence: 99%
“…The high rates of drug resistance, coupled with delays in properly identifying C. auris, and the immunocompromised populations commonly infected by it, are major obstacles in effectively treating C. auris infections. These factors may explain the high mortality rate of 35-60% seen in patients [9,28,29].…”
Section: Challenges Facing Current Antifungalsmentioning
confidence: 99%